La divergence entre la police et la proposition - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1993)
The purpose of this article is to examine the scope of art. 2478 C.c., al. 2, which reads as follows: "ln case of inconsistency between the policy and the application, the latter prevails unless the insurer has in writing indicated the inconsistencies to the policyholder". For example, if the application contains no mention of a particular policy condition, there is, according to the Supreme Court, an inconsistency and therefore, the art. 2478 must be applied. In the following text, the author tries to show the ambiguity of this rule.